The Turnover of Nucleic Acids in Lemna minor - Trewavas, A. (1970)
A method is described for measuring the rate constants of both synthesis and degradation of nucleic acids in sterile growing cultures of Lemna minor which avoids the difficulties of environmental changes in isotope uptake and precursor pool size. In fast growing cultures the half-life of ribosomal RNA has been estimated to be between 5 and 8 days. This half-life has been shown to consist of two components, cytoplasmic ribosomal RNA with a half-life of about 4 days and chloroplast ribosomal RNA with a half-life of about 15 days. The possible interference of recycling has been checked, and the evidence indicates its likely insignificance. “Heavy” labeling of Lemna with D(2)O and (15)NO(−)(3) has provided evidence for the conservation of ribosomal RNA in fast growing cultures and has also provided an alternative assessment of recycling. When Lemna is placed on water, the rate of degradation of ribosomal RNA is increased and that of synthesis is decreased. Under partial “step down” conditions it has been found that omission of either nitrate or phosphate, or calcium or magnesium leads to an increase in the rate of degradation of ribosomal RNA. In Lemna grown on water, benzyladenine increases both the synthetic and degradative rates of nucleic acid metabolism. Abscisic acid, on the other hand, markedly reduces the rate of synthesis of ribosomal RNA but leaves the degradative rate unaltered.